The predictive value of prostate specific antigen density (PSAD) in predicting prostate cancer - Mohd Abdul Rauf bin Paharudin (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Prostate specific antigen (PSA) is a widely use tumor marker for screening of prostate cancer. It is also raised in other benign prostate conditions especially benign prostatic hyperplasia (BPH). Serum PSA is not specific to prostate cancer yet it is still being used as marker for prostate biopsy. Hence, prostate specific antigen density (PSAD) has shown to have ability to distinguish prostate cancer from BPH. The international level of PSAD is 0.15ng/ml/cc. Sparse local data with regard to the PSAD value available. Our aim was to measure the predictive value of PSAD in Pahang population in predicting prostate cancer. This was a case control study of 300 men who underwent transrectal ultrasonography and biopsy (TRUS biopsy) in view of PSA >4ng/ml/cc and/ or abnormal digital rectal examination (DRE).100 patients with positive for prostate cancer and 200 patients with BPH were analysed. The sociodemographic data, PSA, prostate volume, PSAD and histopathology result were recorded and analyzed using IBM SPSS Statistic version 23. The diagnostic validity of PSAD validated using the Receiver Operation Characteristic (ROC) curve analysis. The cutoff point of PSAD for our data is 0.31ng/ml/cc (PPV 73% and NPV 21%) which is higher than the international value 0.15ng/ml/cc (PPV 93% and NPV 62.5%). In our data pool, if an investigator uses the PSAD value of 0.31ng/ml/cc, he will missed 17% patient with prostate cancer. Therefore, we suggest that patients with PSAD between 0.15 and 0.31 to be followed up closely and thus patients in this group has an option for watchful waiting by mean of clinical assessment by digital rectal examination (DRE) and PSA level measurements. We also noted patients with prostate cancer was older, has higher PSA level and smaller prostate volume compares to patient with BPH. In conclusion, PSAD is a good tool in prediction of prostate cancer and can give opportunity to cut the unnecessary prostate biopsy.